Conservative treatment of coccyx fistulas and some perianals - Mañana, Julio; Guicheff, Vladimir (Cirugía del Uruguay, 1972)
Eleven patients with coccygeal and perianal fistulas were treated by injections of fenal in a salution saturated by mineral oil. The paper reports the procedure followed, including the results obtained. We concluded that the method is worth consideration as an elective treatment far coccygeal fistulas and recurrences thereof as well as far sorne perianal fistulas.